SALES SYSTEM AT TEROGONG PHARMACY USING VISUAL BASIC VER. 6.0 - Indrawati Ema Kusumahari; Ir. Syahril Ir. Syahril (Jurnal Sistem Informasi, 2008)
Computers as a support tool that can solve various problems. Computers became animportant part in the organization because of the power of information processingtechnology and the volume of data processed. Computerized data processingtransactions are enabling activities that not only done by large organizations.Computerized sales system is very helpful in processing transactions, and preparingreports. Transaction processing and preparation of reports to be more effective,efficient and timely manner.